2015
DOI: 10.1111/obr.12266
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weight bias and stigma on quality of care and outcomes for patients with obesity

Abstract: Summary The objective of this study was to critically review the empirical evidence from all relevant disciplines regarding obesity stigma in order to (i) determine the implications of obesity stigma for healthcare providers and their patients with obesity and (ii) identify strategies to improve care for patients with obesity. We conducted a search of Medline and PsychInfo for all peer-reviewed papers presenting original empirical data relevant to stigma, bias, discrimination, prejudice and medical care. We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
913
3
33

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 972 publications
(962 citation statements)
references
References 109 publications
13
913
3
33
Order By: Relevance
“…Even 69 healthcare professionals who have chosen a career path specializing in the medical management 70 of obese patients demonstrate anti-fat attitudes, as assessed implicitly in laboratory research 71 (Schwartz, Chambliss, Brownell, Blair, & Billington, 2003). Given these data, it is no surprise 72 that higher weight individuals report avoiding preventive healthcare and suffer from receiving 73 suboptimal medical treatment (Phelan et al, 2015; Wee, McCarthy, Davis, & Phillips, 2000). 74 W e i g h t -n e u t r a l a p p r o a c h e s t o p r o m o t e h e a l t h , a c t i v ely attempt to reduce the perpetuation 75 of weight stigma and promote size acceptance by shifting the focus of interventions away from 76 weight loss (i.e., typical of conventional weight-management programs) to well-being and self-77 care, regardless of weight status (Tylka et al, 2014).…”
Section: -Months Post-randomization Eating Behavior Outcome Measurmentioning
confidence: 99%
“…Even 69 healthcare professionals who have chosen a career path specializing in the medical management 70 of obese patients demonstrate anti-fat attitudes, as assessed implicitly in laboratory research 71 (Schwartz, Chambliss, Brownell, Blair, & Billington, 2003). Given these data, it is no surprise 72 that higher weight individuals report avoiding preventive healthcare and suffer from receiving 73 suboptimal medical treatment (Phelan et al, 2015; Wee, McCarthy, Davis, & Phillips, 2000). 74 W e i g h t -n e u t r a l a p p r o a c h e s t o p r o m o t e h e a l t h , a c t i v ely attempt to reduce the perpetuation 75 of weight stigma and promote size acceptance by shifting the focus of interventions away from 76 weight loss (i.e., typical of conventional weight-management programs) to well-being and self-77 care, regardless of weight status (Tylka et al, 2014).…”
Section: -Months Post-randomization Eating Behavior Outcome Measurmentioning
confidence: 99%
“…Thus, it restricts access to quality health care (Phelan et al. 2015; Puhl and Heuer 2010), creates a significant wage gap in the United States (Colls and Evans 2014; Puhl and Heuer 2009, 2010), and constricts friendships and other types of social support (Brewis et al. 2011; Schaefer and Simpkins 2014).…”
mentioning
confidence: 99%
“…Provider and patient sensitivity and bias have been shown to influence provider diagnosis and treatment of overweight and obesity. 21,46,47 In our study, to avoid possible provider or patient sensitivity to the word obesity, any term indicating overweight or obesity was accepted for diagnosis, and accuracy of the term according to BMI percentile was not studied. It is interesting that a study of hospitalized children by Bradford et al 48 showed that parents underestimate their child' s weight status, but almost all parents in the study expected that providers would monitor BMI during admission and inform them of the results.…”
Section: Discussionmentioning
confidence: 99%